The analysis of blood lead levels changeability over the 5-year observation in workers occupationally exposed to lead. (June 2017) - Dobrakowski, Michał; Boroń, Marta; Kasperczyk, Sławomir; Kozłowska, Agnieszka; Kasperczyk, Aleksandra; Płachetka, Anna; Pawlas, Natalia
The aim of the present study was to compare a group of workers with stable lead levels with a group of workers with fluctuating lead levels in terms of selected hematological, biochemical, and immunological parameters. The examined group included male workers occupationally exposed to lead. Blood lead (PbB) levels were measured every 3 months during the 5-year observation. Based on standard deviation of mean PbB levels, the examined population was divided into two groups: low level of fluctuation (L-SD) and high level of fluctuation (H-SD) groups. The mean and maximal PbB levels were significantly higher in the H-SD group than in the L-SD group by 9 and 22%, respectively. At the same time, the maximal level of zinc protoporphyrin (ZPP) and standard deviation of mean ZPP level were higher in the H-SD group by 29 and 55%, respectively. The maximal level of hemoglobin and white blood cell (WBC) count as well as standard deviation of the mean hemoglobin level and WBC count were higher in the H-SD group by 2, 8, 58, and 24%, respectively. The expression of nuclear factor kappa-B1 gene and telomerase reverse transcriptase gene was significantly greater in the H-SD group than in the L-SD group by 11 and 28%, respectively. Workers occupationally exposed to lead do not represent a homogenous population. Some present stable lead levels, whereas others have fluctuating lead levels. These fluctuations are related to secondary changes in ZPP and hemoglobin levels as well as WBC count.